The Routledge companion to nonprofit management - Anheier, Helmut K.; Toepler, Stefan (Routledge companions in business, management and accounting, 2020)
"Over the past three decades or so, the nonprofit, voluntary, or third sector has undergone a major transformation from a small cottage industry to a major economic force in virtually every part of the developed world as well as elsewhere around the globe. Nonprofit organizations are now major providers of public services working in close cooperation with governments at all levels and increasingly find themselves in competition with commercial firms across various social marketplaces. This transformation has come with ever-increasing demands for enhancing the organizational capacities and professionalizing the management of nonprofit institutions. The Routledge Companion to Nonprofit Management is the first, internationally-focused effort to capture the full breadth of current nonprofit management research and knowledge that has arisen in response to these developments. With newly commissioned contributions from an international set of scholars at the forefront of nonprofit management research, this volume provides a thorough overview of the most current management thinking in this field. It contextualizes nonprofit management globally, provides an extensive introduction to key management functions, core revenue sources and the emerging social enterprise space, and raises a number of emerging topics and issues that will shape nonprofit management in future decades. As graduate programs continue to evolve to serve the training needs in the field, The Routledge Companion to Nonprofit Management is an essential reference and resource for graduate students, researchers, and practitioners interested in a deeper understanding of the operation of the nonprofit sector"--